Response to a critical reader of my essay on melancholy (Colombia Medica, 2023)
With the title “Scientific perspective of emotional management in health professionals,” the reader presents a series of considerations based on “very respectful observations and reflections”, five in total, to which I wish to respond after thanking the Journal and the reader because with its publication it contributes to stimulating the healthy debate that must exist in the field of knowledge that defines human behavior as an object. But first I want to state that, with the publication of my essay, I move away from any mood aimed at managing emotions in health professionals, whatever this means. Like everyone who publishes, I am encouraged by the desire to be read and the critical reader testifies to this, but, following the line of argument of his criticism of my essay, I depart from considering that the readers of this magazine are waiting for healthy recommendations for their ways of life. With Foucault, I share the radical criticism he makes of this type of psychoanalysis - and other so-called behavioral sciences - that tend to become preaching. I suppose (and desire) an adult reader and able to discern with my writing, in favor or not of this content. As in any essay, I use a vital experience that continues to be nourished by conceptual references produced from various areas of knowledge to fulfill one of the essential objectives of any essay: to investigate a topic and involve the reader and, finally, does not require exhaustiveness and declares mandatory the subjectivity of the essayist with total freedom in the structure, the tone and style of the text.